If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y+4)=5(y+6)
We move all terms to the left:
6(y+4)-(5(y+6))=0
We multiply parentheses
6y-(5(y+6))+24=0
We calculate terms in parentheses: -(5(y+6)), so:We get rid of parentheses
5(y+6)
We multiply parentheses
5y+30
Back to the equation:
-(5y+30)
6y-5y-30+24=0
We add all the numbers together, and all the variables
y-6=0
We move all terms containing y to the left, all other terms to the right
y=6
| y=-2^-07*500^2+0.0006*500 | | 12y-10=50 | | -9x=207 | | (3^3x-5)+21=0 | | y=-2E-07*500^2+0.0006*500 | | -4x²+4x+3=0 | | 3^3x-5+21=0 | | 5x-11=4(2x-2) | | 3^(3x-5)+21=0 | | 10x-15+9x+5=180 | | x=3+3/4 | | X^5-2x-3=0 | | 3^2x+5=9^x-2 | | 5x-3=1+8x+13 | | -(d-6)=0 | | 32=20-3h | | x^2(x-1)=4(2x-3) | | 6x-1+4x+11=90 | | b-10/2=-13 | | 3x=8+4x | | x^2(x-1)=4(x-3) | | 31-3b=4 | | 4f-48-18=-2 | | e+11/9=2 | | 39=4b+7 | | i/5+6=11 | | 6-v=4 | | 4/5x-1/2+5/2x=2+3/2x1/4 | | 4x+5=x–8 | | 3(x-5)=7x=12 | | 63/e=9 | | 12=7v+10v |